THE IMPLEMENTATION PROCESS OF TRAINING PROGRAMS IN JORDAN: THE ROLE OF INFORMATION SYSTEMS - Ra'ed (Moh’d Taisir) Masa'deh; Bader Yousef Obeidat (European Scientific Journal, ESJ, 2014)
This paper studies the characteristics of the training process within ten banks in Jordan. In order to achieve a better view of the implementation process and validate the research, the study conducted several interviews in Jordan to collect the primary data of this study. Further, a qualitative research was performed. Having reviewed the existing literature, it was found that three factors may be used to explain the nature of the training process within the ten banks. These factors are the training director’s role, the training challenges, and the information systems training techniques. Lastly, the investigation of the data exposed that all factors are likely to play an essential role in the implementation process within Jordanian banks.